2018
DOI: 10.1109/jsac.2018.2844941
|View full text |Cite
|
Sign up to set email alerts
|

Combination Networks With or Without Secrecy Constraints: The Impact of Caching Relays

Abstract: This paper considers a two-hop network architecture known as a combination network, where a layer of relay nodes connects a server to a set of end users. In particular, a new model is investigated where the intermediate relays employ caches in addition to the end users. First, a new centralized coded caching scheme is developed that utilizes maximum distance separable (MDS) coding, jointly optimizes cache placement and delivery phase, and enables decomposing the combination network into a set virtual multicast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…In [26] the authors study the fundamental limits of secretive coded caching, examining the case of partially known prefetched files. The work in [27] also considers secrecy constraints; it studies a two-hop network architecture known as a combination network, where a layer of relay nodes connects a server to a set of end users. A new centralized coded caching scheme is developed that jointly optimizes cache placement and delivery phase, and enables decomposing the combination network into a set virtual multicast sub-networks.…”
Section: A Information-theoretic Caching Analysismentioning
confidence: 99%
“…In [26] the authors study the fundamental limits of secretive coded caching, examining the case of partially known prefetched files. The work in [27] also considers secrecy constraints; it studies a two-hop network architecture known as a combination network, where a layer of relay nodes connects a server to a set of end users. A new centralized coded caching scheme is developed that jointly optimizes cache placement and delivery phase, and enables decomposing the combination network into a set virtual multicast sub-networks.…”
Section: A Information-theoretic Caching Analysismentioning
confidence: 99%
“…where A (l) (m (l) , r) is the set of uncoded placement schemes in layer l defined in (9) and D(a (1) , . .…”
Section: Formulationmentioning
confidence: 99%
“…Coded caching for device-todevice (D2D) networks has been studied in [12]- [14]. Caching with security requirements have been studied in [9], [15]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…In [10]- [12], Maxmimum Distance Separable (MDS) codes are applied before placement. In particular, [10], [11] show that the upper bound in [7] is achievable for any (h, r) combination network, and [12] shows that even lower delivery rates are achievable. As the results of our work require memory size larger than that of [8] and is uncoded placement, we only compare our results with those from [7].…”
Section: Introductionmentioning
confidence: 98%
“…In their seminal work [1], Maddah-Ali and Niesen modeled the content delivery phase by a shared error-free link from the single server to all users, and they showed that delivery traffic in this shared-link setup can be highly reduced through a joint design of content placement and delivery strategy that exploits multicasting opportunities. The scheme is known as coded caching and has been extended to various settings, e.g., Gaussian broadcast channels [2], multi-antenna fading channels [3]- [5], or combination networks [6]- [11] as considered in this paper. In a (h, r)-combination network, a single server communicates over dedicated error-free links with h relays and these relays in their turn communicate over dedicated error-free links with h r users that have local cache memories.…”
Section: Introductionmentioning
confidence: 99%